Investigation of Thrombosis Volume, Anticoagulants, and Recurrence Factors in Portal Vein Thrombosis with Cirrhosis - Tsuyoshi Suda; Hajime Takatori; Takehiro Hayashi; Rika Horii; Kouki Nio; Takeshi Terashima; Noriho Iida; Masaaki Kitahara; Tetsuro Shimakami; Kuniaki Arai; Taro Yamashita; Tatsuya Yamashita; et al. (Life, 2020)
This retrospective study investigated factors influencing the portal vein thrombosis (PVT) volume and recurrence in 52 cirrhosis patients with PVT from November 2008 to September 2018. All patients were treated with danaparoid sodium with or without additional antithrombin III. Blood platelet counts significantly correlated with the PVT volume (r2 = 0.17; P < 0.01). Computed tomography confirmed recurrence as PVT aggravation was reported in 43 patients, with ≥50% PVT volume reduction following anticoagulation therapy. In 43 patients, recurrence significantly correlated with the pretreatment PVT volume (P = 0.019). Factors influencing recurrence included a Child–Pugh score >8 (P = 0.049) and fibrosis index ≤7.0 based on four factors (FIB-4) (P = 0.048). Moreover, the relationship between recurrence and correlating factors showed that 15 patients who received warfarin experienced recurrence more often when Child–Pugh scores were >8 (P = 0.023), regardless of maintenance treatment. For patients who did not receive warfarin, a PVT volume ≥3.0 mL significantly influenced recurrence (P = 0.039). Therefore, the platelet count influences the PVT volume. The pretreatment PVT volume correlated with recurrence after anticoagulation therapy. According to the Kaplan–Meier curve, risk factors for PVT recurrence after anticoagulation therapy included Child–Pugh scores >8 and FIB-4 ≤7.0. Therefore, the FIB-4 is a unique factor that shows trends opposing other liver function markers.